SISTEM PAKAR UNTUK DIAGNOSA PENYAKIT KUCING BERBASIS WEB MENGGUNAKAN FRAMEWORKCODEIGNITER WEB BASED EXPERT SYSTEM FOR DIAGNOSING CAT DISEASE USING CODEIGNITER FRAMEWORK - Saputra, Deby; Lestari, Uning; Sutanta, Edhy (Jurnal Script, 2015)
ABSTRACTCat is one of popular animal among the people, this make a number of cat lover in Indonesia is very crowded, but that was not balanced with veterinarian availability.This research will develope an expert sistem to diagnose cat disease. An expert system has 11 knowledge base of cat diseases, and using forward chaining as inference engine. Expert system will built with PHP programming language, CodeIgniter framework, and MySQL as DBMS. Expert system will give a first aid output and treatment of disease for cat based on input symptom by user. This expert system is usefull to help public obtaining information about cat diseases and solution is easy and fast. Keywords: expert system, cat disease, forward chaining, CodeIgniter.